Secure Human Communications Based on Biometrics Signals - WU, Yongdong (Institutional Knowledge at Singapore Management University, 2005)
User authentication is the first and probably the most challenging step in achieving secure person-to-person communications. Most of the existing authentication schemes require communicating parties either share a secret/password or know each other's public key. In this paper we suggest a novel user authentication scheme that is easy to use and overcomes the requirements of sharing password or public keys. Our scheme allows two human users to perform mutual authentication and have secure communications over an open channel by exchanging biometrics signals (e. g., voice or video signals). In addition to user authentication, our scheme establishes a secret session key between two users by cryptographically binding biometrics signals with users's Diffie-Hellman public values. Under the assumption that the two communicating persons are familiar with each other's biometrics signals, we show that the scheme is secure against various attacks, including the man-in-the-middle attack. The proposed scheme is highly suitable for applications such as Voice-over-IP